The affluent entrepreneur : 20 proven principles for achieving prosperity - Snow, Patrick, 1969- (Wiley, 2011)
Encourages readers to turn their passions into profitable businesses, whether they be aspiring entrepreneurs or existing entrepreneurs looking for the next big project, and explains the best way to do so.